Methadone Induced Sensorineural Hearing Loss. (29th July 2013) - Saifan, Chadi; Glass, Daniel; Barakat, Iskandar; El-Sayegh, Suzanne
Abstract : Background. Sudden sensorineural hearing loss (SSHL) caused by opiate abuse or overuse has been well documented in the medical literature. Most documented case reports have involved either heroin or hydrocodone/acetaminophen. Recently, case reposts of methadone induced SSHL have been published. Case Report. We present the case of a 31-year-old man who developed SSHL after a methadone overdose induced stupor. He was subsequently restarted on methadone at his regular dose. On follow-up audiometry exams, he displayed persistent moderately severe sensorineural hearing loss bilaterally. Discussion. This case is notable because unlike all but one previously reported case, the patient—who was restated on methadone—did not make a complete recovery. Conclusion . Methadone overuse in rare cases causes SSHL.